Programa de gestão florestal em pequenas propriedades familiares: um estudo de caso no Sul do Brasil - Bernardy, Daniele (2023)
Brazil is among the world is largest tobacco producers, as well as the world is largest exporter of this crop. In the south region of the country, the largest national producer, the main variety planted is Virginia, which needs firewood for drying the leaves, through curing units, with different technological levels. Therefore, the tobacco sector annually demands large amounts of forest biomass, mainly from family farming forests, which are characterized as small properties, whose forest culture helps to reduce tobacco production costs and also generates extra income for the family sustenance. In this way, the objective of this study was to elaborate a forest program, using quality tools that assist in forest planning and management. The study area was delimited in the southern region of Brazil, collecting data in the states of Santa Catarina and Rio Grande do Sul, where questionnaires were applied to 126 rural producers, in the four strategic regions (Costa Doce, Depressão Central, Centro Serra and Norte) and a forest inventory was carried out on the properties that have forest plantations, in order to characterize and provide information about the forests, quantification of demand and supply in each region. Afterwards, the forestry program was carried out through the PDCA cycle (plan, do, check and act) and in each item other tools were used. From the results it was observed that rural properties are considered small, an average of 17.9 ha, about 40% of producers buy firewood for curing tobacco, many of them have more than one forest on the property, 59 % of producers have forest plantations and have an area available for forest expansion. Regarding the demand and supply of firewood, it is possible to observe that the regions of Costa Doce and Norte have selfsufficiency of more than 7 years, which was 9.0 and 14.4 years, respectively, the other regions have self-sufficiency of less than 7 years. In relation to the forestry program, in the plan stage, the description of the stages and processes of forest implantation was carried out with appropriate techniques and choices for the energy purpose and degree of available technology, the tool used was the flowchart, indicating the order in which must be carried out. In the second stage, do, the 5W1H and 5W2H tool was used as a way to monitor activities and provide information. In the third stage, check, the Check-list quality tool was used to detect the main problems and indicate the activities that have already been carried out. In the last step, act, the Brainstorming tool was used, which helped in the creation of ideas related to continuous improvement. With this, it can be concluded that the quality tools can be adapted to the forest reality and can be used for the elaboration of forest programs, in the context of family agriculture, helping in the continuous improvement of the forests.